Sarcopenic Obesity in Postmenopausal Women: Associations Between Fat Mass, Muscle Mass, and Lower Limb Strength in an Indonesian Clinical Cohort - Wendra Wendra; Teguh Tanuwidjaja; Kishanty Hardaningtyas; Aulia Rahma Fazamuthi (Universitas Islam Negeri Sumatera Utara, Medan, 2025)
Sarcopenic obesity is an emerging public health concern, particularly among postmenopausal women. This condition is characterized by increased fat mass and reduced muscle mass, both of which negatively impact quality of life and physical function. This study employed an analytical design with a cross-sectional approach, involving 51 obese women aged 45 years and older who received care atthe Nutrition Clinic of Dustira Hospital. Fat and muscle mass were assessed using Bioelectrical Impedance Analysis (BIA), while leg muscle strength was measured with a leg dynamometer. The chi-square test was used to examine associations between variables due to its suitability for categorical data analysis. Results indicated that the majority of participants were aged 45-55 years, with 52.9% classified as having obesity category I. Descriptive analysis revealed that 66.7% of subjects had elevated fat mass, particularly intramyocellular lipid (IMCL); 80.4% exhibited very low muscle mass; and 58.8% demonstrated poor leg muscle strength. Statistical analysis showed significant associations between fat mass and leg muscle strength (p = 0.003), and between muscle mass and leg muscle strength (p < 0.001). Effect sizes measured using Cramer's V indicated a strong strength of association. These findings underscore the importance of resistance training interventions in managing sarcopenic obesity among postmenopausal women. Enhancing muscle mass and reducing fat mass, especially IMCL, may contribute to improved leg muscle strength and overall quality of life. Keyword: Fat Mass, Leg Muscle Strength, Muscle Mass, Sarcopenic Obesity, Postmenopausal Women.